If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7a + 11b = 0 Solving -7a + 11b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-11b' to each side of the equation. -7a + 11b + -11b = 0 + -11b Combine like terms: 11b + -11b = 0 -7a + 0 = 0 + -11b -7a = 0 + -11b Remove the zero: -7a = -11b Divide each side by '-7'. a = 1.571428571b Simplifying a = 1.571428571b
| 15=m+-9 | | 5n^2+8n-36=0 | | p^2-2px+x^2=y^2 | | 4(x+3)=14 | | t*6-5=15 | | 20/35*45/4= | | 3(4x+6y)=15 | | a*4+4=14 | | M^2+2m-1m-5m-10-1=0 | | x(x+12)=32 | | 7-0.03x=1.72+1.75 | | [4+2]=6 | | (n+8m)(n+3m)-(n+m)(n-4m)=7x | | 5x-2x+6=x+18 | | 3(4-3c)=c-6 | | 3p+5=2p+15 | | 8*x=72 | | -7(f+1)-6=-41f+55 | | x(x-3)(x+3)=0 | | .4y=9 | | 2z+3(x-5)=130 | | 8y-4=36 | | 2x^3-2x^2+6x-6=0 | | 7x-2=-21 | | c(N)=25+0.15 | | 5x^2-40+20=0 | | 9=2+6.7+.6Y | | 8timesx=72 | | 25+3h=49 | | 2,4(x-0,1)-0,26=2,4x-0,4 | | q(3q+4)=4 | | 15y+8=14 |